2015
DOI: 10.1002/jib.265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steeping temperature on the quality of malt andPito(an indigenous Ghanaian drink)

Abstract: Pito is a traditional fermented beverage produced from malted sorghum or millet grains. Steeping is usually performed at 30°C. Limited information exists on the effect of temperature on the characteristics of the malted grains and the Pito. The aim of this work was to study the effect of varying the steeping temperature (30, 35 or 40°C) on the quality of malt and of the Pito brewed from Kadaga sorghum and to specifically determine the diastatic power, extract yield and attenuation limit of the malt. Total solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
4
Order By: Relevance
“…The germinative energy (>97%) for pearl millet and Macia observed in this study is the same as that reported by Pelembe et al, (2002) for pearl millet. Red sorghum germinative energy was in the range of 94%-95% reported by Morrall, Boyd, Taylor, and Walt (1986) and Ebbah et al (2015) for sorghum. However, other studies have found higher (96%-99%) germinative energy (Bekele, Bultosa, & Belete, 2012) for Red sorghum.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The germinative energy (>97%) for pearl millet and Macia observed in this study is the same as that reported by Pelembe et al, (2002) for pearl millet. Red sorghum germinative energy was in the range of 94%-95% reported by Morrall, Boyd, Taylor, and Walt (1986) and Ebbah et al (2015) for sorghum. However, other studies have found higher (96%-99%) germinative energy (Bekele, Bultosa, & Belete, 2012) for Red sorghum.…”
Section: Discussionmentioning
confidence: 88%
“…Germinative energy, that is, the ability of the grain to germinate fully and with vigor, which is essential to normal malting was determined following method used by Ebbah, Laryea, Barimah, and Djameh (2015). This was repeated five independent times (n = 6) per variety.…”
Section: Determination Of Germinative Energymentioning
confidence: 99%
“…O poder diastático é influenciado pela temperatura e pela quantidade de água absorvida durante a imersão. Ebbah et al (2015) reportaram que, a 40 °C, a quantidade de água absorvida pela cultivar (Tabela 1), na imersão, contribui para o alto DP (88,1 SDU g -1 ), devido ao fato de se ter criado um ambiente propício para o desenvolvimento das enzimas. Além disso, o tempo de germinação e a variedade também influenciam o DP.…”
Section: Maltagemunclassified
“…Contudo, as principais dificuldades encontradas no uso do sorgo, na produção cervejas, são a alta temperatura de gelatinização (> 70 °C) e o baixo poder diastático (DP) (OWUAMA, 1997;OGBONNA, 2011). Portanto, o foco das pesquisas tem sido melhorar a qualidade do malte (DJAMEH et al, 2015;EBBAH et al, 2015). Visando usar o sorgo na produção de cervejas, para aproveitar suas potencialidades, é necessário o conhecimento dos fatores que influenciam na qualidade de seu malte e na mosturação; assim, tais informações podem ajudar a identificar o impacto sobre o processo geral.…”
Section: Introductionunclassified
“…In West Africa the consumption of sorghum beverages (alcoholic and nonalcoholic) is common. Examples include: Dolo (Burkina Faso), Burukutu (Ghana), Pito (Ghana), Gowé (Benin) and Ran-noodo 42 . The combination of soghum and maize is called Kunu and is found mainly in northern Nigéria 43 .…”
Section: Sorghum-made Food Productmentioning
confidence: 99%